Case 8 : “I Know You Want It”: Preventing Sexual Aggression in Bars - Lui, Justin (2018)
Brian Patterson is the owner of The Judge & Jester Tavern (JJ’s), a fictitious bar in London’s downtown entertainment district. JJ’s is popular with students from Western University, but a viral Facebook post describing an experience of assault at the bar has generated negative publicity. Coordinators at Western University, Christine Bellis and Maria Lopez, reached out to ask Patterson if he would be interested in partnering with them and the London Police Service to develop a strategy to prevent sexual violence in London’s bars and clubs. Patterson has a deep sense of ownership over JJ’s and is interested in making his bar safer but is also concerned about the response from his bar staff and the success of his business. He begins to brainstorm a list of ideas, drawing from programs that have been implemented around the world. How should they approach this problem within the London community? What will their intervention look like? What resources do they have? What do they need to know in order to proceed